2008
DOI: 10.1175/2007jcli1535.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of New Precipitation and Reconstructed Streamflow Products to Streamflow Trend Attribution in Northern Eurasia

Abstract: River runoff to the Arctic Ocean has increased over the last century, primarily during the winter and spring and primarily from the major Eurasian rivers. Some recent studies have suggested that the additional runoff is due to increased northward transport of atmospheric moisture (and associated increased precipitation), but other studies show inconsistencies in long-term runoff and precipitation trends, perhaps partly due to biases in the observational datasets. Through trend analysis of precipitation, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 50 publications
4
90
0
1
Order By: Relevance
“…Serreze et al (2002) however found only low correlation between P-E and runoff across the pan-Arctic drainage basin, except for the Lena basin. Several studies have discussed a possible contribution of melting permafrost to increased runoff (Serreze et al 2002;Adam and Lettenmaier 2008;Dyurgerov et al 2010), but at least for the Eurasian Arctic, the total volumes of melting permafrost that are needed to explain the long-term runoff increases seem unrealistic (McClelland et al 2004). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serreze et al (2002) however found only low correlation between P-E and runoff across the pan-Arctic drainage basin, except for the Lena basin. Several studies have discussed a possible contribution of melting permafrost to increased runoff (Serreze et al 2002;Adam and Lettenmaier 2008;Dyurgerov et al 2010), but at least for the Eurasian Arctic, the total volumes of melting permafrost that are needed to explain the long-term runoff increases seem unrealistic (McClelland et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Most likely, a combination of several factors has generated the observed runoff changes, and that combination may vary from basin to basin (Adam and Lettenmaier 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For both these extreme cases, no change in U is assumed. In reality, the sea level rise contribution from the river R increase is likely to be somewhere in between these two limiting cases and to be a combination of changes in P − E and M + F, with different relative importance in different geographical regions [Adam and Lettenmaier, 2008]. [24] Several studies have identified increases in poleward moisture transport, which imply that precipitation P has increased and may be a main driver of increasing river runoff in the Arctic [Dyurgerov and Carter, 2004;McClelland et al, 2004McClelland et al, , 2006.…”
Section: Uncertain River Runoff Contribution To Sea Level Changementioning
confidence: 99%
“…[25] With regard to the dW/dt term in the river basins, other recent studies have indicated that it may be significantly nonzero because of both ongoing permafrost thawing [Adam and Lettenmaier, 2008;Lyon et al, 2009;Lyon and Destouni, 2010] and increasing groundwater flow into rivers in Arctic and subarctic basins [Smith et al, 2007]. New analysis of land water storage from Gravity Recovery and Climate Experiment satellite data also indicates negative dW/dt terms for some major Arctic basins, although data are as yet available only for a few years [Ramillien et al, 2008].…”
Section: Uncertain River Runoff Contribution To Sea Level Changementioning
confidence: 99%
“…The model has been used for numerous water and energy balance studies in the U.S. (Abdulla and Lettenmaier, 1997;Nijssen et al, 1997), the Arctic (Adam and Lettenmaier, 2008;Su et al, 2005;Tan et al, 2011;Hamman et al, 2016) and globally (Nijssen et al, 2001a, b, c;Sheffield et al, 2009). One result of these 20 studies has been refinement of the model to better represent key hydrological processes Cherkauer et al, 2003;Liang et al, 1996Liang et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%